2021
DOI: 10.1371/journal.pgen.1009882
|View full text |Cite
|
Sign up to set email alerts
|

A behavioral screen for mediators of age-dependent TDP-43 neurodegeneration identifies SF2/SRSF1 among a group of potent suppressors in both neurons and glia

Abstract: Cytoplasmic aggregation of Tar-DNA/RNA binding protein 43 (TDP-43) occurs in 97 percent of amyotrophic lateral sclerosis (ALS), ~40% of frontotemporal dementia (FTD) and in many cases of Alzheimer’s disease (AD). Cytoplasmic TDP-43 inclusions are seen in both sporadic and familial forms of these disorders, including those cases that are caused by repeat expansion mutations in the C9orf72 gene. To identify downstream mediators of TDP-43 toxicity, we expressed human TDP-43 in a subset of Drosophila motor neurons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 71 publications
1
20
0
Order By: Relevance
“…Two hits were recently identified in an independent genome‐wide screen in TDP‐43‐expressing flies and correspond to fly homologues of ARIDB1 and WAPL, 38 confirming their specificity. MED23 is relevant because subunits of the Mediator complex suppressed TDP‐43 toxicity in another screen 39 and interact with WAPL, 40 suggesting its importance in disease pathogenesis. TUBB2A transcripts were dysregulated in the axonal compartment of TDP‐43‐depleted motor neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Two hits were recently identified in an independent genome‐wide screen in TDP‐43‐expressing flies and correspond to fly homologues of ARIDB1 and WAPL, 38 confirming their specificity. MED23 is relevant because subunits of the Mediator complex suppressed TDP‐43 toxicity in another screen 39 and interact with WAPL, 40 suggesting its importance in disease pathogenesis. TUBB2A transcripts were dysregulated in the axonal compartment of TDP‐43‐depleted motor neurons.…”
Section: Discussionmentioning
confidence: 99%
“…This effect on neuronal survival is directly related to an increase in Gypsy production upon inhibition of apoptosis in hTDP-43 + glia, thus resulting in enhanced RTE-mediated DNA damage in adjacent neurons [ 255 ]. In a follow-up study, SF2-null flies (homologue of human SRSF1; an RNA splicing factor) crossed with RepoTS>TDP43 strain displayed improved locomotion in negative geotaxis assays and enhanced lifespan, indicating a rescue of TDP-43 pathology in glial cells [ 257 ]. Considering SRSF1’s known roles in HIV transcription [ 258 ] and as a mediator in C9orf72 ALS [ 259 ], this work speaks to the role of TDP-43 pathology in the deregulation of ERVs and motor neuron disease, and the involvement of potentially many other co-factors in modulating the expression and control of RTEs.…”
Section: Endogenous Retroviruses and Transposons In Drosophilamentioning
confidence: 99%
“…Several in vivo studies have shown that SRSF1 is found in condensates (Azpurua et al., 2021; Fei et al., 2017; Hammarskjold & Rekosh, 2017; Haward et al., 2021; Ilik et al., 2020; Lamond & Spector, 2003; Li & Wang, 2021). Aberrant condensation behaviors have also been observed in disease states (Azpurua et al., 2021; Ilik et al., 2020; Li & Wang, 2021). Like many other splicing factors, SRSF1 modulates trafficking to the speckles (Tripathi et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…SRSF1 (Serine/Arginine‐Rich Splicing Factor 1, also known as ASF/SF2) is an archetype member of the SR protein family (Cho et al., 2011; Kohtz et al., 1994). Several in vivo studies have shown that SRSF1 is found in condensates (Azpurua et al., 2021; Fei et al., 2017; Hammarskjold & Rekosh, 2017; Haward et al., 2021; Ilik et al., 2020; Lamond & Spector, 2003; Li & Wang, 2021). Aberrant condensation behaviors have also been observed in disease states (Azpurua et al., 2021; Ilik et al., 2020; Li & Wang, 2021).…”
Section: Introductionmentioning
confidence: 99%